Theoretical Aspects of the Design of Fund-Supported Adjustment Programs. (Occasional Papers; Occasional Paper, 1987)
This paper was originally prepared for a seminar of the Executive Board of the Fund. In the seminar, Executive Directors expressed a broad range of views with regard to both the adequacy of the Fund's approach to financial programming and the validity of the analysis presented in this paper.